Pengelolaan Keuangan Berbasis Gusjigang - Sri Mulyani; Falikhatun (Owner : Riset dan Jurnal Akuntansi, 2023)
Financial management has an important role in business operations. Every business is inseparable from what is called "money" including micro business. The purpose of this study is to explore financial management in micro-businesses that apply the philosophy of gusjigang. The methods used in this study are qualitative descriptive. Informants in this study consisted of two micro-business actors who struggled in the business of jenang Kudus and konveksi as well as the Department of Manpower, Industry, Cooperatives, and SMEs of Kudus Regency. The findings in this study of the philosophy of gusjigang consist of three series of words. First, gus which has a good meaning is used as a philosophy related to ethics in managing business finances. Second, ji has the meaning of falsifies applying, and continuing to learn accounting science to realize good financial management. Third, the gang which means trade is finalized by always being creative and innovative in maintaining business survival. The conclusion obtained from the results of this study shows that the philosophy of gusjigang is used as a philosophy and has become a character for micro-businesses in business financial management.